Intense Chemical Weathering at Glacial Meltwater-Dominated Hailuogou Basin in the Southeastern Tibetan Plateau - Li, Xiangying; Ding, Yongjian; Liu, Qiao; Zhang, Yong; Han, Tianding; Jing, Zhefan; Yu, Zhongbo; Li, Qijiang; Liu, Sha (Water, 2019)
Climate warming has caused rapid shrinkage of glaciers in the Tibetan Plateau (TP), but the impact of glacier retreat on the chemical denudation rate remains largely unknown at the temperate glacial basins. The chemical weathering processes were examined at a temperate glacial basin (HLG) in the southeastern TP based on comprehensive data from the supraglacial meltwater, proglacial river water, precipitation and groundwater over two glacier melt seasons in 2008 and 2013. The concentrations of major ions and suspended sediments in river water exhibit a pronounced seasonality and display a close relationship with river discharge, suggesting a strong hydrological control on the chemical and physical weathering processes. Runoff chemistry is dominated by carbonate weathering and sulfide oxidation. HCO3-, Ca2+, and/or SO42- are the dominant ions in meltwater, river water, precipitation and groundwater. For river water, HCO3- and Ca2+ primarily come from calcite weathering, and SO42- is mainly derived from pyrite oxidation. Both solute and sediment fluxes are positively related to river discharge (r = 0.69, p < 0.01 for sediments). The solute flux and yields are 18,095-19,435 tyear(-1) and 225-241 tkm(-2)year(-1), and the sediment load and yields are 126,390 tyear(-1) and 1570 tkm(-2)year(-1), respectively. The solute yields, cationic denudation rate (CDR; 2850-3108 Sigma*meq(+) m(-2)year(-1)) and chemical weathering intensity (CWI; 616-711 Sigma*meq(+) m(-3)year(-1)) at HLG are higher than those at most basins irrespective of the lithology, suggesting more intense weathering in the TP in comparison to other glacial basins worldwide.